1998
DOI: 10.2337/diacare.21.11.1843
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine concentrations in patients with type 1 diabetes.

Abstract: Subnormal tHcy concentrations in male patients, the absence of a sex difference, and the positive association with age indicate that homocysteine metabolism differs between type 1 diabetic patients and control subjects. Homocysteine is unlikely to be of pathogenic significance in patients, particularly male subjects, with early microvascular disease and/or neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…Studies indicate that adults with type 1 DM without evidence of nephropathy have plasma tHcy levels lower than, comparable to, or higher than healthy non-DM controls. [23][24][25][26][27] Renal status varies in persons with DM related to hyperglycemia, duration of diabetes, and progression of nephropathy, reflecting periods of glomerular hyperfiltration and impaired renal function. In a recent study of adults with type 1 DM, plasma tHcy levels were noted to be significantly lower in the subjects with diabetes than in the subjects with diabetic renal disease and elevated creatinine levels or the non-DM healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that adults with type 1 DM without evidence of nephropathy have plasma tHcy levels lower than, comparable to, or higher than healthy non-DM controls. [23][24][25][26][27] Renal status varies in persons with DM related to hyperglycemia, duration of diabetes, and progression of nephropathy, reflecting periods of glomerular hyperfiltration and impaired renal function. In a recent study of adults with type 1 DM, plasma tHcy levels were noted to be significantly lower in the subjects with diabetes than in the subjects with diabetic renal disease and elevated creatinine levels or the non-DM healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced tHcy concentrations have been found in some populations of adults with type 1 diabetes (12,13). Glomerular hyperfiltration has been proposed as the mechanism (14).…”
mentioning
confidence: 99%
“…In patients with type 1 diabetes, some authors have found a significant association between urinary albumin excretion and plasma homocysteine level, 45,46,50,58 while others have not. 55,59 Controversial findings have also been reported in type 2 diabetes with some investigators finding a significant relation between albuminuria and plasma homocysteine level, 34,49,60 while others did not. 11,27,31,61,62 The discrepancies between these studies may relate to the cross-sectional design with limited numbers of patients of different ethnic background, comorbidity, renal function, and vitamin status.…”
Section: Microalbuminuriamentioning
confidence: 92%
“…Studies which have measured renal function and vitamin status in diabetic patients and control subjects suggest that they have similar plasma homocysteine levels. 45,50,55 This is in agreement with observations from the Hoorn Study, a large population-based study of glucose tolerance and cardiovascular disease in 50-75-yearold subjects in The Netherlands, which showed that the median plasma homocysteine level was similar in subjects with normal glucose tolerance (11.2 µmol/L, interquartile range (IQR) 9.2-14.4, n = 288), impaired glucose tolerance (12.2 µmol/L, IQR 9.7-14.5, n = 170) and diabetes mellitus (11.2 µmol/L, IQR 9.2-13.6, n = 173). 57 In contrast, two studies reported a significantly lower homocysteine concentration in diabetic patients on hemodialysis compared to nondiabetic patients on hemodialysis after adjustment for creatinine, but not for folate, in serum.…”
Section: Determinants Of Plasma Homocysteine Concentrationmentioning
confidence: 98%
See 1 more Smart Citation